Qualitative Evaluation of User Acceptance Readiness to the Implementation of the Health Center Management Information System (SIMPUS) at the South Tangerang City Health Center - Sholihah, Siti Ma'rufatus; Subiyakto, Aang; Ratnawati, Suci; Azizah, Miftakhul Nuuril (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2022)
The success of implementing an Information System (IS) depends on how the system is run by its users. User readiness plays an essential role in ensuring the successful implementation of new technology or system. To improve the quality of health services, the South Tangerang City Health Center has implemented the Health Center Management Information System (SIMPUS), but it is not following its objectives. The implementation of SIMPUS further hampers the smooth running of health services and the performance of the Puskesmas. This study aims to understand the level of user acceptance of SIMPUS implementation and explore the factors that influence it. The study used the Technology Readiness Acceptance Model (TRAM) and qualitative methods to explore data that could not be obtained from quantitative research by collecting interview data and Focus Group Discussion (FGD). The results show that the Technology Readiness Index factor influences the dimensions of the Technology Acceptance Model. Perceived usefulness significantly affects the intention to use SIMPUS to encourage acceptance of SIMPUS implementation. In contrast, insecurity does not affect perceived usefulness in SIMPUS use because users have not optimally used SIMPUS